Simple Science Experiment Learning Design to Improve Children's Critical Thinking Ability - Nurkholisoh, Diah; Syaodih, Ernawulan (International Conference on Elementary Education, 2021)
This study aims to develop a science learning design using experimental methods in improving children's critical thinking skills. The critical thinking indicator applied in this research is the child's ability to express questions and statements based on their analysis of the experimental activities carried out. The research subjects were group B in two different kindergartens using the Design-Based Research (DBR) method through 4 stages, namely 1) problem identification and analysis, 2) developing a prototype solution based on theory 3) conducting an iterative process to test and improve 4) reflecting on product design principles. The conclusions and results of this study are the design of science learning through experimental methods in the form of a structure that includes science themes, competency formulations and developmental achievement indicators, descriptions of science material for teachers, scenarios, and learning evaluations.